Exploring trends of wastewater treatment by using nano-materials and their composites with bio-polymer - Shivani Rauthan; Ajay Singh (Environment Conservation Journal)
Industries have employed various wastewater treatment methods and techniques to reduce pollution load, including biological oxygen demand (BOD), chemical oxygen demand (COD), total suspended solids (TSS), total dissolved solids (TDS), color, and toxic metals. This review paper aims to highlight and analyze various water treatments with special focus on the use of nanomaterials and their composites with biopolymers. Many other techniques for wastewater treatment (WWT) have been developed using nanotechnology. These techniques are usually based on nanofiltration, disinfection, adsorption and biosorption, photocatalysis, and sensing technology. Techniques like fluorescence in situ hybridization (FISH) are used for clarification of composition, amount analysis, and dispensing of various bacterial groups in biofilms and granules. By review, it can be concluded that when the old primary water treatment technique is clubbed with nano-composite adsorption, composites containing specific biopolymers such as starch, chitosan, collagen, or cellulose-lignin materials can effectively adsorb nearly 100% of harmful metals such as arsenic, cadmium, mercury, lead, and chromium (As, Cd, Hg, Pb, Cr) from wastewater while also effectively removing color. Enhancing therapeutic efficacy, longevity, safety, and cost-effectiveness requires research into these methods.